Legalitas Narkotika Jenis Baru (Kratom) : Antara Ancaman dan Peluang bagi Ketahanan Nasional Indonesia - Martha Istyawan; Ahmat Fadholi; Dian Surtikanthi; Sri Annisya; Utari Dwi Pratiwi (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The legality of kratom (Mitragyna speciosa) has become a polemic in Indonesia because of the prohibition on the use of kratom in traditional medicines and food supplements which cause a sedative-narcotic effect. But on the other hand, many farmers depend on kratom as an economic commodity. This study aims to see the extent of social control related to kratom in Indonesia and abroad. By doing so, it is hoped that it can help policy makers implement better policies against kratom so as to improve Indonesia's defense in the narcotics sector. The research was conducted through a literature study conducted on 20 journals and 9 modules related to the production, distribution, consumption and control of kratom in Indonesia and abroad. The results of the study found that so far the regulations related to kratom in Indonesia are still unclear. Overall, there is still no regulation that prohibits kratom cultivation and distribution or The only existing regulation is Circular Letter Number HK.04.4.42.421.09.16.1740 of 2016 from BPOM regarding the ban on the use of kratom in traditional medicine and health supplements because it causes a sedative-narcotic effect. This opens up opportunities for the production and distribution of kratom in Indonesia and marketing in foreign countries. For this reason, preventive and repressive control of kratom is necessary and regulations that regulate not only the use of kratom, but also the production and distribution of kratom in Indonesia.marketing of kratom leaves in Indonesia.